Maternal Report of Infant Emotional Well‐Being Following Their Infant's Hospitalization for Neonatal Cardiac Surgery. Issue 4 (24th June 2013) - Jordan, Brigid; Franich‐Ray, Candice; Anderson, Vicki; Northam, Elisabeth; Albert, Nadia; Cochrane, Andrew; Menahem, Samuel
ABSTRACT Little is known about the immediate impact of neonatal cardiac surgery on emotional and behavioral functioning in infancy. This exploratory, qualitative study investigated if infants who underwent cardiac surgery in the first 3 months of life exhibited emotional and behavioral dysregulation or traumatic stress responses. Ninety‐one infants and their mothers were recruited while inpatients. Mothers were interviewed about their perceptionof the impact of illness, surgery, and the hospitalizationon on their infant 4 weeks after discharge. Responses were analyzed by two coders using thematic analysis. Eighty‐three of the mothers interviewed described impacts on the infant, which emcompassed five themes: infant behavior (n = 44, 48%), emotions (n = 43, 47%), physical health (n = 31, 34%), relationship and social interaction (n = 27, 30%), and development (n = 18, 20%). Our expectation that there would be impacts in the period soon after neonatal cardiac surgery consistent with a pediatric medical traumatic stress response model was supported. Maternal report of infant well‐being following neonatal cardiac surgery delineated three groups of infants: those who appear unscathed; those who appear generally happy, but demonstrate specific alarm and avoidance responses in the presence of medical trauma; and those with significant problems in emotional regulation, behavioral regulation, or both.